Migracja wewnętrzna w UE oraz EOG a problem nielegalnego rynku pracy. Analiza sytuacji imigrantów z Polski zamieszkujących okręg Hordaland - Nowiak, Wojciech; Narożna, Dominika; Cappelen, Cornelius (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2016)
Niniejsze opracowanie jest wynikiem pracy międzynarodowego zespołu badawczego i dotyczy funkcjonowania Polaków na nielegalnym rynku pracy w Norwegii. Badania zostały oparte na wywiadach pogłębionych, przeprowadzonych wśród imigrantów z Polski, zamieszkujących okręg Hordaland, którego centrum administracyjnym jest miasto Bergen. Ukazuje ono charakter tego rynku pracy oraz zasady i motywy funkcjonujących na nim pracowników z Polski.

This study is the result of an international research team and concerns the functioning of Poles in the illegal labor market in Norway. The study is based on in-depth interviews conducted among Polish immigrants, living in Hordaland county, whose administrative center is the city of Bergen. It shows the nature of the labor market and the principles and motives of Poles that function on the labor market.
Internal migration within the EU and EEA vis-à-vis black labor market. An analysis of the situation of Polish immigrants living in Hordaland county
Keywords: migracja zarobkowa; Polacy w Norwegii; undeclared work; black labor; the black economy; informal employment